Faktor-Faktor yang Mempengaruhi Kejadian Menopause Dini di Desa Kalirejo Kecamatan Kalipare Kabupaten Malang - Nita Dwi Astikasari; Nasifah Tuszahroh (Universitas STRADA Indonesia, 2019)
Some women menopause at less than 40 years age, called early menopause. One of the factors affect is age of menarche, parity and contraception. The purpose of this study to determine the factors influence incidence early menopause in Kalirejo Village, Kalipare District, Malang Regency. The research design used is correlation analysis with cross sectional approach. Sampling using simple random sampling with number respondents 195 women. Data collection using questionnaire sheets. The analysis technique used is logistic regression with the help SPSS for Windows 20. The results obtained by the value ρ-value for menarche age factor 0.002 <0.05, maternal parity factors 0.043 <0.05, contraception factors 0.021 <0, 05, then Ha is accepted, tendency there is influence age of menarche, maternal parity, contraception with incidence early menopause in Kalirejo Village, Kalipare District, Malang Regency.